Safety and Tolerability of Human Placenta-Derived Cells (PDA001) in Treatment-Resistant Crohn’s Disease: A Phase 1 Study - Mayer, Lloyd; Pandak, William M.; Melmed, Gil Y.; Hanauer, Stephen B.; Johnson, Kristine; Payne, Denise; Faleck, Herbert; Hariri, Robert J.; Fischkoff, Steven A. (Inflammatory bowel diseases, 2013)
The clinical utility of cellular therapies is being investigated in a broad range of therapeutic areas. This phase 1 study represents the first exploration of PDA001, a preparation of cells cultured from human placental tissue, in subjects with Crohn's disease. Twelve subjects with active, moderate-to-severe Crohn's disease unresponsive to previous therapy were given 2 intravenous infusions of PDA001 1 week apart, monitored weekly for 5 weeks, and assessed at 6 months, 1 year, and 2 years after infusion. Six subjects received 2 infusions of 2 × 10 cells (low dose), and 6 subjects received 2 infusions of 8 × 10 cells (high dose). Mean baseline Crohn's Disease Activity Index in the low-dose and high-dose groups was 305 and 364, respectively, and mean C-reactive protein was 8 mg/L and 49 mg/L, respectively. All subjects in the low-dose group achieved a clinical response (a Crohn's Disease Activity Index decrease of ≥70 points versus baseline), and 3 achieved remission (a Crohn's Disease Activity Index decrease of ≥100 to <150 points). Two subjects in the high-dose group achieved response, and none met remission criteria. Most adverse events were mild to moderate in severity and included headache, nausea, fever, and infusion site reactions. PDA001 infusions appear safe and well-tolerated in subjects with treatment-resistant Crohn's disease. A response was seen in all subjects in the low-dose group. The high-dose group, with a higher baseline disease activity, had only 2 responders, suggesting a more treatment-resistant population. A phase 2 study in this patient population is ongoing.